State Regulation of Special Economic Zones in Russia - BOYKO, Natalya Nikolaevna; USMANOVA, Rezida Miniyarovna (Journal of Advanced Research in Law and Economics, 2018)
This article presents a comparative analysis of ʼspecial economic zonesʼ with an established business regime for each of them. These zones are created either in the territory of the constituent entities of the Russian Federation or in the territory of one or several municipal entities. The regulatory framework for all entities is created at the federal and regional levels through the adoption of relevant laws. Formally, all the ʼspecial zonesʼ have different goals, but are really focused on attracting investments by creating special conditions for doing business and providing tax benefits. This in turn, attracts the creation of new jobs, the satisfaction of the population in high-quality services and allows the population to live a comfortable and self-fulfilling lifestyle. This article analyses the special regimes for the implementation of entrepreneurial and investment activities existing in Russia, in particular territories. The characteristic features of these territories, which have the right to state support, tax preferences and incentives, are highlighted. The results of the study confirm that being residents of the territory of special zones, they receive significant tax advantages in comparison with non-residents. The availability of these territories with special business regimes positively affects the efficiency for business and regional budgets and will improve the material well-being of the living population.